2020
DOI: 10.1007/jhep08(2020)138
|View full text |Cite
|
Sign up to set email alerts
|

Holographic QFTs on S2×S2, spontaneous symmetry breaking and Efimov saddle points

Abstract: Holographic CFTs and holographic RG flows on space-time manifolds which are d-dimensional products of spheres are investigated. On the gravity side, this corresponds to Einstein-dilaton gravity on an asymptotically AdSd+1 geometry, foliated by a product of spheres. We focus on holographic theories on S2× S2, we show that the only regular five-dimensional bulk geometries have an IR endpoint where one of the sphere shrinks to zero size, while the other remains finite. In the Z2-symmetric limit, where the two sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…There may be a distributional limit for the source term which exactly matches the behavior of the CdL solution as Λ → ∞, but this is not evident 53. Similar solutions where discussed for general S d 1 × S d 2 foliations in pure gravity[51], and recently for S 2 × S 2 foliations in Einstein-dilaton theory[52].…”
mentioning
confidence: 81%
“…There may be a distributional limit for the source term which exactly matches the behavior of the CdL solution as Λ → ∞, but this is not evident 53. Similar solutions where discussed for general S d 1 × S d 2 foliations in pure gravity[51], and recently for S 2 × S 2 foliations in Einstein-dilaton theory[52].…”
mentioning
confidence: 81%
“…Efimov resonances were also found that were explored in [35] to generate a class of associated black hole solutions. The general case of QFTs on S 2 × S 2 was addressed in [17].…”
Section: Jhep10(2023)188mentioning
confidence: 99%
“…We can instead define the boundary conditions on the gravity side in order to accommodate the CdL geometry as an allowed solution. Provided one can do this consistently, 52 this defines a different field theory on the cylinder, which does not admit the global AdS solution as one its states. This theory can only be extended up to a finite global time, at which point the time-evolution reaches a singularity as a consequence of an infinite instantaneous "kick" at ψ = π/2.…”
Section: Jhep09(2021)065mentioning
confidence: 99%
“…The relevant expansions are given in [13,16] and we refer the reader to these works for details. Without loss of generality we consider a UV fixed point at an extremum of V at ϕ = 0 with the potential in the vicinity 53 Similar solutions where discussed for general S d 1 × S d 2 foliations in pure gravity [51], and recently for S 2 × S 2 foliations in Einstein-dilaton theory [52].…”
Section: Jhep09(2021)065mentioning
confidence: 99%